The creative cosmos beyond humans: a symphony of participatory design and visual artificial intelligence - Zhao, YangYang (Frontiers in Communication, 2024)
As artificial intelligence (AI) continues to pervade our daily lives, expanding the boundaries of participatory design to include aspects of visual communication beyond humans is imperative. This research explores the intriguing convergence of participatory design and AI-enabled visual-based design as powerful methodologies for shaping the creation of new ideas (e.g., products/services). The specific research objectives are 3-fold: to unravel the nuanced dynamics in terms of perception inherent in the increasingly intertwined visual communication between humans and AI (e.g., sketch AI); to investigate how AI-enabled visual communication supports the participatory process with stakeholders; and to explore their experiences in AI-enabled visual-based design for non-human subjects (e.g., animals and plants). A laboratory study of 18 experimental groups found that AI-enabled visual-based design significantly enhances creative ideation performance when (novice) designers engage AI as a partner rather than merely a tool or collaboratively interact with stakeholders. Notably, the engagement level of internal stakeholders is much higher than that of external stakeholders.